Selected Macro-Economic Variables and Financial Leverages Impact on Performance Indicators of Quoted Chemical Firms in PSX - Ali, Muhammad Uzair; Ahmad, Nawaz (Journal of Asian Business Strategy, 2020)
This research paper scrutinizes the correlation between one of financial leverage tool i.e. capital structures and financial performance variables of firms with the evidence from quoted companies from chemical sector in Pakistan Stock Exchange (PSX) during 2004-2015. To estimate the relationship between capital structure and performance variables we selected three profitability ratios i.e. net profit margin, return on assets and return on equity, whereas for capital structure an important leverage ratio, D:E is selected as independent variable. Credit to GDP ratio and lending interest rate are also included in model as independent control variables. The results concluded that interest rate has insignificant effect on performance of firms. However, leverage ratio and credit to GDP ratio has relatively significant relationship with all performance variables. The outcomes through this study are consistent with the findings of earlier researches. Forthcoming work can be done to probe different industries using other new financial performance variables.